PEMBERDAYAAN SDM DESA WANGUNHARJA DALAM PENGEMBANGAN UKM KERIPIK PARE - Karyono Karyono; Ifah Masrifah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Human Resource Empowerment provides a welfare life for the village community has the ability to change and improve the socio-economic life of its people. This Community Service activities are one part of Tri Dharma institution that must be implemented by the academic community, especially Lecturers and Students. The goal is the development of SME management of Pare Chips for Family Welfare Programme in Wangunharja Village as partners to get their additional income in improving the economy of their families by making processed Pare Chips made from bitter melon create people interested and want to try. The quality of Human Resources is based on coaching/training, we hold training in making Pare Chips for the development of SMEs in improving knowledge, skills, insights and opportunities for Partners as a solution to fill free time and utilize the existing time. The method uses counselling, discussion, Q&A, the practice of processing bitter melon chips and teaches how to package the product as eye catching Pare Chips. Bitter melon is one type of vegetable with a distinctive green colour and bitter taste, typical bitter taste in bitter melon then most people do not like it a lot, with it processed into Pare Chips that are not bitter is expected to be a healthy snack for the family. The result is that the fostered partners are able to create a variety of flavoured bitterness chips independently and will become a new sources of income for households as well as being its flagship product.